Application of Raney Al-Ni Alloy for Simple Hydrodehalogenation of Diclofenac and Other Halogenated Biocidal Contaminants in Alkaline Aqueous Solution under Ambient Conditions - Bendová, Helena; Kamenická, Barbora; Weidlich, Tomáš; Beneš, Ludvík; Vlček, Milan; Lacina, Petr; Švec, Petr (Materials (Basel, Switzerland), 2022)
Raney Al-Ni contains 62% of Ni2Al3 and 38% NiAl3 crystalline phases. Its applicability has been studied within an effective hydrodehalogenation of hardly biodegradable anti-inflammatory drug diclofenac in model aqueous concentrates and, subsequently, even in real hospital wastewater with the aim of transforming them into easily biodegradable products. In model aqueous solution, complete hydrodechlorination of 2 mM aqueous diclofenac solution (0.59 g L-1) yielding the 2-anilinophenylacetate was achieved in less than 50 min at room temperature and ambient pressure using only 9.7 g L-1 of KOH and 1.65 g L-1 of Raney Al-Ni alloy. The dissolving of Al during the hydrodehalogenation process is accompanied by complete consumption of NiAl3 crystalline phase and partial depletion of Ni2Al3. A comparison of the hydrodehalogenation ability of a mixture of diclofenac and other widely used halogenated aromatic or heterocyclic biocides in model aqueous solution using Al-Ni was performed to verify the high hydrodehalogenation activity for each of the used halogenated contaminants. Remarkably, the robustness of Al-Ni-based hydrodehalogenation was demonstrated even for the removal of non-biodegradable diclofenac in real hospital wastewater with high chloride and nitrate content. After removal of the insoluble part of the Al-Ni for subsequent hydrometallurgical recycling, the low quantity of residual Ni was removed together with insoluble Al(OH)3 obtained after neutralization of aqueous filtrate by filtration.
Keywords: nickel alloy; reductive dechlorination; hydrometallurgy; biocide; water treatment; NaBH4; drug